Ethnomathematics Study: Mathematical Concepts in Bima Weaving Motifs - Isnaniah Isnaniah; M. Imamuddin; Annisa Annisa (STAI Hubbulwathan Duri, 2023)
This study aimed to discover and investigate the mathematical concepts present in muna Mbojo (Bima weaving). This study was an ethnographic research, and employed a descriptive approach. This study's information was derived from observations and document reviews of Bima woven fabrics. The data was obtained using documentation by collecting the types or motifs of Bima weaving. Subsequently, in-depth observationswere conducted on the collected weaving. The data was analysed through reduction, presentation, and verification/conclusion. The results of the study found by the researchers namely: 1) bali motif (line motif) discovered mathematical concepts, including lines, rectangles, squares, and parallels; 2) wunta motif (flower motif) discovered mathematical concepts, including lines, sigsag lines/curves, angles, triangles, rhombuses, circles, alignments, symmetrical, translation/shifts, and reflections; and 3) kakando motif (bamboo shoots motif). Bima weaving is rich in motifs, weaving motifs that are generally produced by Bima people are bali motifs (lines), wunta motifs (flowers), and kakando motifs (bamboo shoots). In these motifs many mathematical concepts are found such as line, zigzag/curved line, angle, rectangle, square, triangle, rhombus, circle, alignment, symmetry, translation/shift, and mirroring. These mathematical concepts found in Bima weaving can be used by teachers to help or facilitate elementary school students in learning and understanding mathematical concepts. Learning mathematics will be more meaningful if teachers are able to involve students' culture in constructing their knowledge in the learning process.